Bone Morphogenetic Protein 15 Knockdown Inhibits Porcine Ovarian Follicular Development and Ovulation - Qin, Yufeng; Tang, Tao; Li, Wei; Liu, Zhiguo; Yang, Xiaoliang; Shi, Xuan; Sun, Guanjie; Liu, Xiaofeng; Wang, Min; Liang, Xinyu; Cong, Peiqing; Mo, Delin; et al. (Frontiers in Cell and Developmental Biology, 2019)
Bone morphogenetic protein 15 (BMP15) is strongly associated with animal reproduction and woman reproductive disease. As a multifunctional oocyte-specific secret factor, BMP15 controls female fertility and follicular development in both species-specific and dosage-sensitive manners. Previous studies found that BMP15 played a critical role in follicular development and ovulation rate in mono-ovulatory mammalian species, especially in sheep and human, but study on knockout mouse model implied that BMP15 possibly has minimal impact on female fertility of poly-ovulatory species. However, this needs to be validated in other poly-ovulatory species. To investigate the regulatory role of BMP15 on porcine female fertility, we generated a BMP15-knockdown pig model through somatic nuclear transfer technology. The BMP15-knockdown gilts showed markedly reduced fertility accompanied by phenotype of dysplastic ovaries containing significantly declined number of follicles, increased number of abnormal follicles, and abnormally enlarged antral follicles resulting in disordered ovulation, which is remarkably different from the unchanged fertility observed in BMP15 knockout mice. Molecular and transcriptome analysis revealed that the knockdown of BMP15 significantly affected both granulosa cells (GCs) and oocytes development, including suppression of cell proliferation, differentiation, and follicle stimulating hormone receptor (Fshr) expression, leading to premature luteinization and reduced estradiol (E2) production in GCs, and simultaneously decreased quality and meiotic maturation of oocyte. Our results provide in vivo evidence of the essential role of BMP15 in porcine ovarian and follicular development, and new insight into the complicated regulatory function of BMP15 in female fertility of poly-ovulatory species.